Effect of primary alpha phase variation on mechanical behaviour of Ti–6Al–4V alloy. (September 2015) - Sahoo, R.; Jha, B. B.; Sahoo, T. K.
Abstract : Small punch tests (SPTs) have been carried out at room temperature to correlate the microstructural variation of Ti–6Al–4V alloy with that of SPT parameters. Microstructural variation in terms of different volume fractions of primary alpha phase of Ti–6Al–4V alloy has been introduced as a result of solution annealing at different temperatures followed by thermal aging. Small punch test parameters, i.e. total area under the load vs displacement curve, area under the zone of elastic bending, plastic bending and plastic instability have been found to increase from the content of 10% primary alpha phase to 20% primary alpha phase and then these are decreasing from the content of 20% primary alpha phase to 30% primary alpha phase.